Green Marketing : A Systematic Literature Review - Premi, Hansini; Sharma, Monica; Dangayach, G. S. (Indian Journal of Marketing, 2021)
Firms’ marketing strategies and consumer perception towards green products have been evolving quickly, and the emergence of the 'green world' is a reality now. This paper summarized an in-depth study of research papers, articles, and reports since 1990 and also provided insights into the consumer behavior in responding to, adopting the green products, and identifying the factors (whether personal factors or environmental factors) which are responsible for the significant inclination and rise in consumption of green products. The literature review highlighted that the benefits of using green products and their association with others like environment, biodiversity, and ecological sustainability were not successfully and effectively communicated to the consumers. It was also observed that competition in creating a brand in their respective categories, environmental values, and economic objectives are almost in sync with the green marketing philosophy and environmental values, but since green products are perceived as premium category products, consumers’ buying decisions in favor of them was doubtful. The study also shed light on the future course to be adopted by the marketers in formulating sustainable green marketing strategies with the help of functional and emotional ‘green positioning.’ The review of studies suggested that the rise of ‘green brands’ in developing nations has begun. The paper’s uniqueness is that it summarized the works of some of the most prominent authors, and it also captured the classification of articles based on source, country, time, and theme. It would help the readers understand the evolution of green marketing.